Quantitative Proteomic Analysis of Four Developmental Stages of Saprolegnia parasitica - Srivastava, Vaibhav; Rezinciuc, Svetlana; Bulone, Vincent (Frontiers in Microbiology, 2018)
Several water mold species from the Saprolegnia genus infect fish, amphibians and crustaceans in natural ecosystems and aquaculture farms. Saprolegnia parasitica is one of the most severe fish pathogens. It is responsible for millions of dollars of losses to the aquaculture industry worldwide. Here, we have performed a proteomic analysis, using gel-based and solution (iTRAQ) approaches, of four defined developmental stages of S. parasitica grown in vitro, i.e., the mycelium, primary cysts, secondary cysts and germinated cysts, to gain greater insight into the types of proteins linked to the different stages. A relatively high number of kinases as well as virulence proteins, including the ricin B lectin, disintegrins and proteases were identified in the S. parasitica proteome. Many proteins associated with various biological processes were significantly enriched in different life cycle stages of S. parasitica. Compared to the mycelium, most of the proteins in the different cyst stages showed similar enrichment patterns and were mainly related to energy metabolism, signal transduction, protein synthesis and post-translational modifications. The proteins most enriched in the mycelium compared to the cyst stages were associated with amino acid metabolism, carbohydrate metabolism and mitochondrial energy production. The data presented expand our knowledge of metabolic pathways specifically linked to each developmental stage of this pathogen.